The Efforts of the Family Welfare Empowerment Driving Team in Increasing Entrepreneurial Motivation for Family Welfare Empowerment Cadres during the COVID-19 Pandemic - Juliasih, Nenden; Nurhayati, Sri; Rukanda, Nandang (Society, 2022)
This study aims to examine the efforts of the Family Welfare Empowerment Team in increasing the entrepreneurial motivation of Family Welfare Empowerment cadres in Gadobangkong Village, Ngamprah District, West Bandung Regency. The research method uses a descriptive method with a qualitative approach. The research instruments used in data collection were observation, interviews, and documentation studies which were analyzed qualitatively. There were 10 (ten) research subjects, consisting of 1 (one) Head of the Family Welfare Empowerment Driving Team and 9 (nine) members of the Family Welfare Empowerment Driving Team. From the results of data analysis, it was found that the efforts made by the Family Welfare Empowerment Driving Team, namely 1) The Family Welfare Empowerment Driving Team provided entrepreneurship training to increase entrepreneurial motivation for Family Welfare Empowerment cadres through training as much as 80% 2) The inhibiting factors of the Family Welfare Empowerment Driving Team to increase entrepreneurial motivation Family Welfare Empowerment cadres, in general, are capital, individual will, inadequate infrastructure and time. 2) The assistance and guidance provided by the Family Welfare Empowerment Driving Team are still low due to time constraints and immature experience. The recommendation in this study is to hold further training with varied materials, which are more interesting, and bring in competent resource persons so that Family Welfare Empowerment cadres are more motivated in entrepreneurship.